The implication of information technology on the audit profession in developing country: Extent of use and perceived importance. Issue 2 (2nd May 2017) - Tarek, Menna; Mohamed, Ehab K.A.; Hussain, Mostaq M.; Basuony, Mohamed A.K.
Abstract : Purpose: Information technology (IT) largely affected contemporary businesses, and accordingly, it imposes challenges on the auditing profession. Several studies investigated the impact of IT, in terms of the extent of use of IT audit techniques, but very studies are available on the perceived importance of the said issue in developing countries. This study aims to explore the impact of implementing IT on the auditing profession in a developing country, namely, Egypt. Design/methodology/approach: This study uses both quantitative and qualitative data. A survey of 112 auditors, representing three of the Big 4 audit firms as well as ten local audit firms in Egypt, is used to gather preliminary data, and semi-structured interviews are conducted to gather details/qualitative-pertained information. A field-based questionnaire developed by Bierstaker and Lowe (2008) is used in this study. This questionnaire is used first in conducting a pre-test, and then, the questionnaire for testing the final results is developed based on the feedback received from the test sample. Findings: The findings of this study reveal that auditors' perception regarding client's IT complexity is significantly affected by the use of IT specialists and the IT expertise of the auditors. Besides, they perceive that the new audit applications' importance and the extent of their usage are significantly affected by the IT expertise of the auditors. The results also reveal that the auditors' perception regarding the client's IT is not affected by the control risk assessment. However, the auditors perceive that the client's IT is significantly affected by electronic data retention policies. The results also indicated that the auditors' perception regarding the importance of the new audit applications is not affected by the client's type of industry. The auditors find that the uses of audit applications as well as their IT expertise are not significantly affected by the audit firm size. However, they perceive that the client's IT complexity as well as the extent of using IT specialists are significantly affected by the audit firm size. Research limitations/implications: This study is subject to certain limitations. First, the sample size of this research is somehow small because it is based on the convenience sampling technique, and some of the respondents were not helpful in answering the surveys distributed for this research's purpose. This can be attributed to the fear of the competitors that their opponent may want to gather information regarding their work to be able to succeed in the competition in the market so they become reluctant to provide any information about their firm. Even some people who were interested to participate were not having enough time because the surveys were distributed during the high season of their audit work and there was limited time for the research to be accomplished. Hence, it is difficult to generalize the results among all the audit firms in Egypt because this limits the scope of the analysis, and it can be a significant obstacle in finding a trend. However, this can be an opportunity for future research. Second, the questionnaire is long and people do not have enough time to complete it. This also affected the response rate. In addition to this, the language of the questionnaire was English, so some respondents from the local audit firms were finding difficulty in understanding some sophisticated IT terms. Practical implications: This study makes some recommends/suggestions that can well be used to solve some practical problems regarding the issues concerned. This study focuses on accounting information system (AIS) training during the initial years of the auditors' careers to help staff auditors when they become seniors to be more skilled with AIS expertise needed in today's audit environment. Clear policy statements are important to direct employees so that IT auditors evaluate the adequacy of standards and comply with them. This study suggests increasing the use of AIS to enhance individual technical and analytical skill sets and to develop specialized teams capable of evaluating the effectiveness of computer systems during audit engagements. This study further recommends establishing Egyptian auditing standards in this electronic environment to guide the auditors while conducting their audit work. Social implications: Auditors should prioritize causes of risks and manage them with clear understanding of who receives them, how they are communicated and what action should be taken in a given community/society. So, they have to determine and evaluate all risks according to the client's type of industry (manufacturing, non-financial services and financial). Auditors also have to continually receive feedback on the utility of continuous auditing (CA) in assessing risk. In particular, it is better for the auditor to determine how the audit results will be used in the enterprise risk management activity performed by the management. In addition, privacy has several implications to auditing, and so, it has to be reflected in the audit program and planning as well as the handling of assignment files and reports. Alike, retention of electronic evidence for a limited period of time may require the auditor to select samples several times during the audit period rather than just at year end. Originality/value: As mentioned, this study is conducted within a developing country's context. The use and importance of IT is reality of time. However, very few studies are devoted to explore the use/importance of IT in auditing in developing countries, and thus, this study carries a significance to have better understanding about it. Moreover, knowledge of how IT is used, the related risks and the ability to use IT as a resource in the performance of audit work is essential for auditor effectiveness at all levels including developing countries.